2017
DOI: 10.3382/ps/pex059
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for exercise during pullet rearing, Part I: Effect on the musculoskeletal characteristics of pullets

Abstract: Increased load-bearing exercise improves bone quality characteristics in a variety of species, including laying hens. Providing increased opportunities for exercise during the pullet rearing phase, a period of substantial musculoskeletal growth, offers a proactive approach to reducing osteoporosis by improving bone composition. The main objective of this study was to determine whether differing opportunities for exercise during rearing influences pullet musculoskeletal characteristics. Two flock replicates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 35 publications
5
50
4
Order By: Relevance
“…This coincides with observations on commercial farms that assessed damage via both dissection (Kolakshyapati et al, 2019) and palpation (Larsen et al, 2018) and found no association between individual ranging and keel damage. It was expected that rearing with structural enrichments may have reduced the later occurrence of fractures (Casey-Trott et al, 2017b), but this was not supported by the current study. The actual relationship between range use and keel damage might be inconclusive because painful keel fractures might prevent birds passing through the pop holes (Richards et al, 2012) and ultimately reduces range access.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…This coincides with observations on commercial farms that assessed damage via both dissection (Kolakshyapati et al, 2019) and palpation (Larsen et al, 2018) and found no association between individual ranging and keel damage. It was expected that rearing with structural enrichments may have reduced the later occurrence of fractures (Casey-Trott et al, 2017b), but this was not supported by the current study. The actual relationship between range use and keel damage might be inconclusive because painful keel fractures might prevent birds passing through the pop holes (Richards et al, 2012) and ultimately reduces range access.…”
Section: Discussioncontrasting
confidence: 86%
“…This would also correspond with the higher empty gizzard weight observed in the ranging hens, similar to findings of larger gizzards in free-range versus caged hens (Yang et al, 2014). The reduction in body weight might also be a result of greater energy utilisation during locomotion, although greater exercise opportunities have previously been shown to increase bone and muscle development (Casey-Trott et al, 2017a;Regmi et al, 2016) which was not found in the outdoor hens. Other measured skeletal properties rather than overall mass may have revealed differences between ranging groups although recent work showed no effect of ranging on multiple tibial measurements across hens from a commercial aviary-free-range system (Kolakshyapati et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This would also correspond with the higher empty gizzard weight observed in the ranging hens, similar to findings of larger gizzards in free-range versus caged hens (Yang et al, 2014). The reduction in body weight might also be a result of greater energy utilisation during locomotion, although greater exercise opportunities have previously been shown to increase bone and muscle development (Casey-Trott et al, 2017a;Regmi et al, 2016) which was not found in the outdoor hens. Other measured skeletal properties rather than overall mass may have revealed differences between ranging groups although recent work PeerJ reviewing PDF | (2019:11:43210:2:0:NEW 3 Feb 2020)…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it is well documented both within Australia and internationally that range use varies by individual choice with some hens ranging daily while others do not range at all (Larsen et al, 2017;Pettersson et al, 2016b). This variation could result in large differences in activity and diet between hens which may impact health and welfare such as influencing body composition by lowering body fat accumulation (Crespo & Esteve-Garcia, 2001;Renema et al, 1999;Sun et al, 2006) and strengthening the bones (Regmi et al, 2016) and muscles (Casey-Trott et al, 2017a ). Although recent work with commercial freerange layers showed no relationship between range use and tibial bone strength (Kolakshyapati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%